2010
DOI: 10.3201/eid1604.090107
|View full text |Cite
|
Sign up to set email alerts
|

Community-associated Methicillin-ResistantStaphylococcus aureusStrains in Pediatric Intensive Care Unit1

Abstract: Endemicity may lead to increased resistance and virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
(48 reference statements)
3
45
0
1
Order By: Relevance
“…17,19 Our findings corroborate these data, since CA-MRSA isolates have been identified only in the anal and oropharyngeal sites.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…17,19 Our findings corroborate these data, since CA-MRSA isolates have been identified only in the anal and oropharyngeal sites.…”
supporting
confidence: 81%
“…isolates colonizing patients that are frequent users of healthcare services and with a serious underlying disease, with these factors having been pointed out in the literature as important risk factors for colonization with VRE. 17,23 When analyzing the positivity of the investigated sites, anal and oropharyngeal swabs showed a higher positivity rate for S. aureus, whereas nasal swabs yielded the highest positivity for Enterococcus spp., respectively 25%, 25% and 20%.…”
mentioning
confidence: 99%
“…Review of the reference lists of all the included articles yielded 1 additional eligible study. Among the 18 eligible studies, 2 had partially overlapping data, 24,25 and the maximum relevant information was extracted (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The studies provided screening data on 19 722 neonatal and pediatric patients. More specifically, 11 studies reported data on 12 284 screened neonates in 12 NICUs, whereas 6 studies reported data on 7107 children hospitalized in 6 PICUs.…”
Section: Figurementioning
confidence: 99%
“…CA-MRSA strains have most commonly been SCCmec type IV and Panton-Valentine leukocidin positive, while HA-MRSA strains have most commonly been SCCmec types I, II, and III and Panton-Valentine leukocidin negative. However, recent studies describing CA-MRSA strains in the hospital setting (17,27,33) suggest that clinical presentation and epidemiologic risk factors are no longer sufficient to reliably define molecular strain types. CA-MRSA infections have been demonstrated to be more common in children, especially children less than 2 years of age (12).…”
Section: Discussionmentioning
confidence: 99%